2009
DOI: 10.2337/dc09-1232
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of the Diabetes Care Protocol, a Multifaceted Computerized Decision Support Diabetes Management Intervention That Reduces Cardiovascular Risk

Abstract: OBJECTIVEThe Diabetes Care Protocol (DCP), a multifaceted computerized decision support diabetes management intervention, reduces cardiovascular risk of type 2 diabetic patients. We performed a cost-effectiveness analysis of DCP from a Dutch health care perspective.RESEARCH DESIGN AND METHODSA cluster randomized trial provided data of DCP versus usual care. The 1-year follow-up patient data were extrapolated using a modified Dutch microsimulation diabetes model, computing individual lifetime health-related cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 24 publications
0
39
0
1
Order By: Relevance
“…25 The other 12 trials had a cluster randomized design, 6,11,[13][14][15][16][17]19,[27][28][29][30][31][32][33][34] and 10 trials adjusted for clustering in the analysis. 6,11,14,16,[30][31][32][33][34][35] Twelve trials reported a power calculation for a specified difference between groups and a specific outcome.…”
Section: Methodological Validity Assessment (Table 1)mentioning
confidence: 99%
See 3 more Smart Citations
“…25 The other 12 trials had a cluster randomized design, 6,11,[13][14][15][16][17]19,[27][28][29][30][31][32][33][34] and 10 trials adjusted for clustering in the analysis. 6,11,14,16,[30][31][32][33][34][35] Twelve trials reported a power calculation for a specified difference between groups and a specific outcome.…”
Section: Methodological Validity Assessment (Table 1)mentioning
confidence: 99%
“…Three studies only showed improvements in the process of care. Improvements were found in yearly HbA1c testing, retinal exams, and the composite of three tests, as well as in laboratory monitoring, 18 low-density lipoprotein testing, and the composite of all Cleveringa et al, [15][16][17] Phillips et al 14 and Ziemer et al, 6 and MacLean et al 19 and Khan et al 18 represent the same respective study with different outcome parameters. a Value in randomized column is 1 if patients were randomized or when cluster randomization with the generalized estimating equation (GEE) was used.…”
Section: Effectiveness Of a Cdss Alone (Table 2)mentioning
confidence: 96%
See 2 more Smart Citations
“…Om de kosteneffectiviteit te vergroten zullen huisartsen zich moeten richten op patiënten met de hoogste cardiovasculair risico's en zich daarbij niet moeten concentreren op verdergaande verlaging van de HbA1c-waarde. 15 …”
Section: Hoe Kosteneffectief Is De Diabeteszorg?unclassified